Altering Nature
X, 346 p.
Keywords: The two volumes of Altering Nature consider the complex ways that concepts of 'nature' and 'the natural' are understood and the relevance of those understandings to discussions of biotechnology. Volume One, Concepts of 'Nature' and 'The Natural' in Biotechnology Debates, offers nuanced accounts of the ways that nature is invoked and interpreted, both descriptively and prescriptively, by different disciplines, including perspectives from spirituality and religion, philosophy, science and medicine, law and economics, and aesthetics. In the context of that broad discussion, Volume Two, Religion, Biotechnology, and Public Policy, reviews recent religious and ethical analyses of four specific areas of biotechnology: assisted reproduction, genetic therapy and enhancement, human-machine incorporation, and biodiversity. It identifies and explores the richer normative themes that inform particular debates and suggests ways that policy choices in biotechnology may be illuminated by devoting greater attention to religious perspectives.